A novel phase retrieval method from three-wavelength in-line phase-shifting interferograms based on positive negative 2π phase shifts. Issue 1 (2nd January 2018) - Xu, Xiaoqing; Wang, Yawei; Ji, Ying; Xu, Yuanyuan; Xie, Ming
Abstract: A new method to extract quantitative phases for each wavelength from three-wavelength in-line phase-shifting interferograms is proposed. Firstly, seven interferograms with positive negative 2 π phase shifts are sequentially captured by using the phase-shifting technique. Secondly, six dc-term suppressed intensities can be achieved by the use of the algebraic algorithm. Finally, the wrapped phases at the three wavelengths can be acquired simultaneously from these six interferograms add-subtracting by employing the trigonometric function method. The surface morphology with increased ambiguity-free range at synthetic beat wavelength can be obtained, while maintaining the low noise precision of the single wavelength measurement, by combining this method with three-wavelength phase unwrapping method. We illustrate the principle of this algorithm, and the simulated experiments of the spherical cap and the HeLa cell are conducted to prove our proposed method, respectively.